Pembelajaran Akidah Akhlak melalui Pengelompokan Kelas Berbasis Gender untuk Siswa Kelas IX - Savira Rahmadhea, Savira Rahma (STAI Ma'had Aly Al-Hikam Malang, 2022)
Abstract: The application of class grouping between male and female students is a policy that is rarely found in formal schools in Indonesia. With the application of class grouping between male and female students, it is expected to be able to improve the morals of the students through the learning of moral aqidah. This study intends to find out 1) the application of gender-based class grouping in aqidah moral learning, 2) supporting and inhibiting factors for implementing gender-based class grouping in learning aqidah morality 3) the impact of the application of gender-based class grouping in learning morals. The research method used is descriptive qualitative method. Based on the results of the study, the application of gender-based class grouping in the learning of aqidah morality in class IX is that the learning conditions of class students are increasingly conducive and learning becomes more focused and male students and female students are able to grow self-control against the opposite sex and form akhlaq karimah from each class. habituation carried out by madrasas. Keywords: Learning Akhlak Akidah, Class Grouping, Gender. Abstrak: Penerapan pengelompokan kelas antara siswa laki-laki dan perempuan merupakan kebijakan yang jarang ditemui di sekolah formal di Indonesia. Dengan penerapan pengelompokan kelas antara siswa laki-laki dan perempuan diharapkan mampu meningkatkan akhlakul kharimah siswa-siswinya melalui pembelaharan akidah akhlak. Penelitian ini bermaksud untuk mengetahui 1) penerapan pengelompokan kelas berbasis gender dalam pembelajaran akidah akhlak, 2) faktor-faktor pendukung dan penghambat penerapan pengelompokan kelas berbasis gender dalam pembelajaran akidah akhlak, 3) dampak penerapan pengelompokan kelas berbasis gender dalam pembelajaran akidah akhlak. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Berdasarkan hasil penelitian, penerapan pengelompokan kelas berbasis gender dalam pembelajaran akidah akhlak di kelas IX yaitu kondisi belajar siswa kelas yang semakin kondusif dan belajar menjadi lebih terarah serta siswa laki-laki dan siswa perempuan mampu menumbuhkan kontrol diri terhadap lawan jenis dan membentuk akhlakul karimah dari setiap pembiasaan yang dilakukan oleh madrasah